Does pressurized carbon dioxide lavage improve bone cleaning in cemented arthroplasty? - Knappe, Kevin; Stadler, Christian; Innmann, Moritz Maximilian; Schonhoff, Mareike; Gotterbarm, Tobias; Renkawitz, Tobias; Jäger, Sebastian (Applied Sciences, 2021)
Cemented implant fixation in total joint arthroplasty has been proven to be safe and reliable with good long-term results. However, aseptic loosening is one of the main reasons for revision, potentially caused by poor cementation with low penetration depth in the cancellous bone. Aim of this prospective laboratory study was, to compare impact pressure and cleaning effects of pulsatile saline lavage to novel carbon dioxide lavage in a standardized carbon foam setup, to determine whether or not additional use of carbon dioxide lavage has any impact on cleaning volume or cleaning depth in cancellous bone. Carbon specimens simulating human cancellous bone were filled with industrial grease and then underwent a standardized cleaning procedure. Specimens underwent computed tomography pre- and post-cleaning. Regarding the impact pressure, isolated carbon dioxide lavage showed significant lower pressure compared to pulsatile saline lavage. Even though the combination of carbon dioxide lavage and pulsatile saline lavage had a positive cleaning effect compared to the isolated use of pulsatile saline lavage or carbon dioxide lavage, this was not significant in terms of cleaning volume or cleaning depth.
Gesehen am 13.08.2021